The quiet revolution in agri-food distribution (wholesale, logistics, retail) in Sub-Saharan Africa - Reardon, Thomas; Awosuke, Titus; Haggblade, Steven; Minten, Bart; Vos, Rob (Alliance for a Green Revolution in Africa, 2019)
This chapter explores the Quiet Revolution in the distribution segments spurred by those drivers. We examined the growth, structure and conduct of the segments, from wholesale and logistics, to retail. The chapter: (1) discusses the myths about traders and logistics, and the lack of systematic data, that are holding back sufficient useful policy debate; (2) presents findings from important new survey-based studies in several African countries to illustrate the dynamic changes occurring in the wholesale/logistics segment, and aspects of their relations with farmers; and (3) summarizes findings and presents recommendations to the public sector integrated with an enumeration of constraints facing in particular traders and logistics firms.